Lean participative process improvement: outcomes and obstacles in trauma orthopaedics - New, S; Hadi, M; Pickering, S; Robertson, E; Morgan, L; Griffin, D; Collins, G; Rivero-Arias, O; Catchpole, K; McCulloch, P (Public Library of Science, 2016)
OBJECTIVES: To examine the effectiveness of a "systems" approach using Lean methodology to improve surgical care, as part of a programme of studies investigating possible synergy between improvement approaches. SETTING: A controlled before-after study using the orthopaedic trauma theatre of a UK Trust hospital as the active site and an elective orthopaedic theatre in the same Trust as control. PARTICIPANTS: All staff involved in surgical procedures in both theatres. INTERVENTIONS: A one-day "lean" training course delivered by an experienced specialist team was followed by support and assistance in developing a 6 month improvement project. Clinical staff selected the subjects for improvement and designed the improvements. OUTCOME MEASURES: We compared technical and non-technical team performance in theatre using WHO checklist compliance evaluation, "glitch count" and Oxford NOTECHS II in a sample of directly observed operations, and patient outcome (length of stay, complications and readmissions) for all patients. We collected observational data for 3 months and clinical data for 6 months before and after the intervention period. We compared changes in measures using 2-way analysis of variance. RESULTS: We studied 576 cases before and 465 after intervention, observing the operation in 38 and 41 cases respectively. We found no significant changes in team performance or patient outcome measures. The intervention theatre staff focused their efforts on improving first patient arrival time, which improved by 20 minutes after intervention. CONCLUSIONS: This version of "lean" system improvement did not improve measured safety processes or outcomes. The study highlighted an important tension between promoting staff ownership and providing direction, which needs to be managed in "lean" projects. Space and time for staff to conduct improvement activities are important for success.